Anti-eye-fatigue device system / Muhammad Ammar Hafiz Md Arfan ... [et al.] - Md Arfan, Muhammad Ammar Hafiz; Shamris, Muhammad Haziq Dzikri; Mohd Kamil, Muhammad Noor Amin; Saiful Anar, Nur Farzana Syahirah; Husaini, Yusnira (2024)
IT specialists who spend extended periods staring at their laptop, phone, and computer monitor at close range face the risk of compromised eyesight and related visual health issues. The continuous near-distance visual concentration without adequate breaks, coupled with the blue light emitted by digital screens, leads to eye strain, dryness, redness, blurred vision, headaches, and increased sensitivity to light. These symptoms can negatively impact IT specialists' productivity, job satisfaction, and overall well-being. Implementing effective solutions and strategies to mitigate the adverse effects of prolonged screen usage on their eyesight and promote proper eye care practices is crucial. The Anti Eye-Fatigue Device System consists of two inputs: distance detected by the ultrasonic sensor and light intensity detected by the LDR sensor. Data from the sensor will be sent to the web server and displayed. This system focuses on adding monitoring and alerting features for laptop and computer users as these devices are often used in the IT field in their work.